PERAN AKTOR DALAM PENGEMBANGAN WISATA KAMPUNG PELANGI DI KELURAHAN RANDUSARI KECAMATAN SEMARANG SELATAN KOTA SEMARANG - Pramesti, Retha; Kismartini, Kismartini; Suwitri, Sri (Journal of Public Policy and Management Review, 2024)
The Kota Tanpa Kumuh (KOTAKU) policy was implemented by the Mayor of Semarang with the aim of overcoming problems related to housing and slum areas in Semarang City, especially in the Kampung Pelangi area. The implementation of the KOTAKU policy involves several actors, namely the government, the private sector, and the community with different roles. This research aims to analyze the role of actors as well as supporting factors and inhibiting factors in the role of actors in the development of Pelangi Village tourism in Randusari Village. This research uses qualitative methods through a descriptive approach and is conducted by observation and interviews based on purposive sampling techniques. The results showed that the role of actors in the development of Pelangi Village tourism, namely actors who act as policy makers, has functioned well, but to optimize the policy, the involvement of other actors is needed. Actors who act as coordinators have not run optimally. All government actors act as facilitators, both physical and non-physical. However, private actors as facilitators have not performed their roles optimally. Actors who act as implementers have not been optimal, especially for Pokdarwis and communities who experience obstacles in managing tourist attractions. Supporting actors are tasked with following the direction of the Semarang City Government. Then in developing Kampung Pelangi tourism, there are also several factors that become supporters and obstacles.